Discharge Behavior of Mg–Sn–Zn–Ag Alloys with Different Sn Contents as Anodes for Mg-air Batteries. Issue 2 (2nd January 2020) - Gu, Xiong-Jie; Cheng, Wei-Li; Cheng, Shi-Ming; Yu, Hui; Wang, Zhi-Feng; Wang, Hong-Xia; Wang, Li-Fei
Abstract : Controlling the microstructure and discharge performance of Mg-based alloys is of great importance and aimed at optimizing magnesium anode materials to the level required for power source applications. In this study, the microstructure along with discharge properties of extruded Mg–Sn–Zn–Ag alloys with Sn content ranging from 2 wt.% to 8 wt.% are investigated. The results indicate that the Mg–4Sn–1Zn–1Ag alloy exhibits the most negative discharge potential during the half-cell test than the other alloys investigated in this study. Moreover, a Mg-air battery with a Mg–4Sn–1Zn–1Ag alloy as the anode provides a relatively high cell voltage together with power density compared with the counterpart battery. Furthermore, the microscopic mechanism of an anode material exhibiting an excellent discharge performance is systematically discussed in terms of the second phase, dynamic recrystallization, crystal orientation and discharge product film.